Sensibility and resistance profiles to antibiotics of pathogens isolated in a hospital unit of food and nutrition - Di Primio, Eliza Marques; Schumacher, Bianca de Oliveira; Preuss, Edcarlos; Menezes, Dulcinéa Blum; Gandra, Eliezer Ávila; Helbig, Elizabete (Acta Scientiarum. Health Sciences, 2017)
The objective of this study was to evaluate the sensibility and resistance profiles to antibiotics of pathogens isolated in a hospital unit of food and nutrition. It was evaluated as sample spots, with repetitions, environmental samples, utensils, equipment, manipulators’ hands and usually diet that would be served to the hospitalized patients. In the evaluated samples, coagulase positive Staphylococcus (CPS) and Gram negative bacillus were enumerated, and also, it was possible to isolate Klebsiella spp and Escherichia coli. The antimicrobial of less efficiency for CPS was oxacillin and penicillin-G, and for Klebsiella spp ampicillin e cephalothin. It should be emphasized that it was found strains multiresistants of CPS, Klebsiella spp and E. coli. The hospital unit of food and nutrition was evaluated as microbiological inadequate in several points, and it was verified resistance profiles to antibiotics of pathogens isolated in this unit.